The Effect of Xmn -1 Polymorphism and Coinheritance of Alpha Mutations on Age at First Blood Transfusion in Iranian Patients with Homozygote IVS 1-5 Mutation - Mozhgan Hashemieh; Zahraalsadat Saadatmandi; Azita Azarkeivan; Hossein Najmabadi (International Journal of Hematology-Oncology and Stem Cell Research, 2022)
Background: Thalassemia syndromes are the most prevalent hereditary hemoglobinopathies in the world. Iran is located on the thalassemia belt.  In this study, the effect of Xmn -1 polymorphism and coinheritance of alpha mutations on age at first transfusion as well as transfusion interval in Iranian thalassemic patients with homozygous Intervening Sequence (IVS) 1-5 mutation was assessed.